2019
DOI: 10.3174/ajnr.a6374
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carotid Plaque Components by Quantitative Susceptibility Mapping

Abstract: BACKGROUND AND PURPOSE: Intraplaque hemorrhage in the carotid artery is related to an increased risk of cerebrovascular ischemic events. We aimed to investigate whether quantitative susceptibility mapping can characterize carotid artery plaque components and quantify the severity of intraplaque hemorrhage. MATERIALS AND METHODS: For this ex vivo quantitative susceptibility mapping study, 9 carotid endarterectomy specimens were imaged on a 3T MR imaging scanner using a 3D multi-echo gradient-echo sequence and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…In diseased arterial tissue, key components of the tissue microstructure, such as collagen fibers, smooth muscle cells, and elastic lamina, become disrupted, impairing vessel function 60 . A number of recent studies have demonstrated the application of QSM for imaging carotid plaque in vivo, highlighting that many technical challenges associated with imaging carotid arteries using QSM in a clinical setting can be overcome 9‐13 . These studies have demonstrated marked improvement in the depiction of intraplaque hemorrhage and calcification in vivo but have largely ignored differences in regional plaque susceptibility that may be driven by compositional variations in the microstructure of fibrotic plaque tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In diseased arterial tissue, key components of the tissue microstructure, such as collagen fibers, smooth muscle cells, and elastic lamina, become disrupted, impairing vessel function 60 . A number of recent studies have demonstrated the application of QSM for imaging carotid plaque in vivo, highlighting that many technical challenges associated with imaging carotid arteries using QSM in a clinical setting can be overcome 9‐13 . These studies have demonstrated marked improvement in the depiction of intraplaque hemorrhage and calcification in vivo but have largely ignored differences in regional plaque susceptibility that may be driven by compositional variations in the microstructure of fibrotic plaque tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative susceptibility mapping (QSM) is an MRI method capable of spatially mapping the magnetic susceptibility of biological tissue. [6][7][8] Recently, a number of studies have applied QSM to carotid plaques and demonstrated marked improvement in intraplaque hemorrhage and calcification depiction compared to conventional multi-contrast MRI [9][10][11][12][13] based on the inherent differences between the magnetic susceptibilities of these structures: calcifications are diamagnetic, whereas hemorrhages are paramagnetic. 14 1.…”
Section: Qsmmentioning
confidence: 99%
“…The signal intensity of IPH on MP-RAGE or other T1-weighted images depends on the acuity of blood products. It is known that IPH experiences a dynamic degradation process, successively in the form of deoxyhemoglobin, methemoglobin, and hemosiderin [23] . Among these blood products, methemoglobin is considered to be a source of high signal intensity because of its reduced T1.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MR signal may be complex due to the distribution and concentration of methemoglobin. A chronic inflammatory cascade incited by atherosclerosis can lead to a smaller apparent volume of IPH that over time leads to hemosiderin deposition or sequestration within foamy macrophages [23] . This is supported by histologic findings of erythrocyte membranes and iron present within the necrotic cores of atherosclerotic coronary plaques even in the absence of recent hemorrhage [24] .…”
Section: Discussionmentioning
confidence: 99%
“…. A number of recent studies have demonstrated the application of QSM for imaging carotid plaque in vivo, highlighting that many technical challenges associated with imaging carotid arteries using QSM in a clinical setting can be overcome[9][10][11][12][13] . These studies have demonstrated marked improvement in depiction of IPH and calcification in vivo but have largely ignored differences in regional plaque susceptibility that may be driven by compositional variations in the microstructure of fibrotic plaque tissue.…”
mentioning
confidence: 99%